Asymmetric effect of agriculture value added on CO2 emission: Does globalization and energy consumption matter for pakistan - Khurshid, Nabila; Khurshid, Jamila; Shakoor, Usman; Ali, Kashif (Frontiers in Energy Research, 2022)
Globalization has resulted in several technical advancements, including the ability to connect people all over the world and drive the economies with higher agricultural output. With agricultural productivity expanding quickly, the negative impact of globalization on environmental degradation is being disregarded. Rapid agricultural expansion and globalization have resulted in significant increases in energy consumption and CO2 emissions. The primary purpose of this research is to assess the role of Pakistan’s massive agriculture industry in encouraging or discouraging CO2 emissions under Globalization scenario. Therefore, we applied Non-linear Autoregressive Distributive Lag Nonlinear Autoregressive Distributed Lag model from 1971 to 2021. Our results showed that in presence of globalization, agricultural production shows asymmetries in case of positive and negative shocks. A positive shock in Agricultural production increased the CO2 emissions while negative shock in agricultural production decreased CO2 emissions. Furthermore, GDP, energy consumption and economic globalization have positive association with economic globalization while on the other hand, surprisingly trade and urbanization in the presence of globalization have negative association with CO2 emissions. Environmental deterioration due to greenhouse emissions causes climatic variation in the economy and several mitigation strategies are required on sustainable basis in Pakistan. So, our study recommends that farmers of Pakistan should adopt organic farming this will help to reduce CO2 emissions.